Einfluss von Maltose-modifizierten Polyethylenimin-Nanopartikeln auf mesenchymale Stammzellen und Osteoblasten - Lautenschläger, Friedrich Stefan; Justus Liebig University Giessen (My University, 2017)
In unserer alternden Gesellschaft wird die effektive Behandlung von Erkrankungen des Skelettsystems eine zunehmend komplexere Aufgabe. Beim lokalen oder systemischen Einsatz von neuartigen Materialien, wie beispielsweise Nanopartikeln, sind komplexe Interaktionen und Auswirkungen ihres Einsatzes zu berücksichtigen. Mesenchymale Stammzellen sind mit ihrer Differenzierungskapazität in die verschiedenen osteogenen sowie chondrogenen Zelllinien geeignetes Untersuchungssystem im Bereich des Knochenstoffwechsels, um neuartige nanopartikuläre Funktionsmaterialien einem ersten in-vitro Test zu unterziehen. Eine Quelle für vitale MSC ist Bohrmehl, welches bei unfallchirurgischen Eingriffen anfällt. Aus ihm lassen sich, durch geeignete Wahl des Kulturmediums, vitale, differenzierungsfähige MSC gewinnen. Ein Vorteil der direkten Gewinnung aus Spendermaterial ist die Verfügbarkeit von Zellen verschiedener Individuen. Spenderabhängige Variabilitäten der Auswirkungen der getesteten Materialien lassen sich so besser darstellen als bei Verwendung nur einer Zelllinie. Im Vorfeld zu in-vivo Untersuchungen müssen diese Materialien umfassend in-vitro untersucht werden, um potentiell erwünschte sowie unerwünschte Effekte frühzeitig zu erkennen. Dendritische Moleküle wie beispielsweise Polyethylenimin sind interessante Kandidaten für die systemische sowie lokale Anwendung im lebenden Organismus. Sie sind relativ einfach und in großen Mengen synthetisierbar und werden gut in die Zelle aufgenommen. Modifikationsmöglichkeiten ergeben sich insbesondere durch Substitution der endständigen Amino-Gruppen beispielsweise durch verschiedene Zucker oder aber durch Größen- und Verzweigungsvariation des PEI-Kerns. Sie sind geeignete nicht-virale Vektoren, um beispielsweise DNA oder siRNA in die Zelle zu transportieren. Im unmodifizierten Zustand weisen die PEI Moleköle eine relativ hohe Toxizität gegenüber Zellen auf, hauptsächlich durch positive Ladungen verursacht. Zuckersubstituenden wie beispielsweise im hier untersuchten Fall Maltose, reduzieren die Toxizität durch Reduktion der positiven Gesamtladung deutlich. Wir untersuchten den Einfluss von zwei PEI Nanopartikeln mit unterschiedlichem PEI-Kern (25000 mg/mol sowie 5000 mg/mol) auf vier MSC von unterschiedlichen Spendern welche bei unfallchirurgischen Eingriffen gewonnen wurden. Die Aufnahme der Nanopartikel in die Zelle wurde mittels Transmissions sowie Fluoreszenzmikroskopie entsprechend markierter Partikel untersucht.

The development of effective treatments of diseases of the muscolo-scelettal system is one major task for future research. The application of novel materials, like nanoparticles for example, requires intensive investigations of interactions and effects. Mesenchymal Stemcells are capable to differentiate in different cells like osteoblasts, chondroblasts or adipocytes. They are suitable to investigate novel nanoparticular materials regarding their influence on the bone metabolism. A source of vital MSC is reaming debris, harvested during trauma surgery. Harvested from different donors, they are capable to reveal donor-to-donor variabilities in the cellular reactions on administered materials and pharmaceutics. Preliminary to in-vivo experiments, in-vitro tests are necessary for the early detection of adverse effects. Dendritic molecules, like Polyethylenimine for example, are promising candidates for the systemic or local application in living organisms. They feature easy synthesis and a good cellular uptake. They can be modified by changing the PEI core or by substitution of their Amino-groups with different other groups. PEI nanoparticles are efficient non-viral vectors for the DNA and si-RNA transfection of cells. Unmodified PEI features a relative high toxicity, mainly due to positive charges of the Amino-groups. By substitution of Amino-groups with Maltose as an example the positive charge can be reduced, enhancing the biocompatibility. We investigated the influence of two different, Maltose modified PEI nanoparticles, with different weights of the PEI core (STP2508 25000 mg/mol and STP2755 5000 mg/mol) and the same Maltose modification on four different MSC, harvested from individual donors in trauma surgery. The uptake of the nanoparticles has been monitored by TEM and Fluorescence Microscopy for incubation times of 1h to 24 h. After 24 h the incorporated nanoparticles feature a perinuclear distribution. The toxicity has been investigated by TEM, optical microscopy and functional assays (LDH- assay) for incubation times of 24 h and 72 h. The observed toxicity was strongly dependent on the nanoparticle concentration, 1 mg/ml and 50 µg/ml have been used, and the weight of the PEI core particle. Exclusively the heavier particle resulted in an increased toxic response from most, pronounced for the fast proliferating MSC. Negative influences from the nanoparticles in optical microscopy could be impressively detected after prolonged incubation times of one week. To determine the total cell count the DC protein assay has been calibrated. Long term investigations of 7 days, 21 days and 28 days yielded in a concentration dependent reduction of cellular proliferation for both nanoparticles, statistically significant after 21 days, respective 28 days. To check if the medium containing nanoparticles has an influence on the osteogenic differentiation a series of trials with nanoparticle concentrations of 1 µg/ml, 20 µg/ml and 50 µg/ml for both nanoparticles and incubation times of 7 days, 21 days and 28 days have been conducted. The normalized Alkaline Phosphatase activity per cell has been measured and histomorphometric evaluation of von-Kossa stained samples has been undertaken. Despite a certain trend towards an increase in as well ALP activity as mineralization for osteogenic medium containing 20 µg/ml of STP2508 no statistically significant result could be reached. While not certainly osteoinductive, the nanoparticles tested here are no obstacle for the osteogenic differentiation at all. In conclusion the heavier nanoparticle STP2508 posesses a certain toxicity for both tested concentrations. Both nanoparticles slow down cellular growth. The osteogenesis is not negatively influenced by addition of the nanoparticles.
Keywords: ddc:610